Ch1 (Vitis vinifera L.) Rootstock Control of Scion Response to Water Stress in Some Commercial Grapevine Cultivars - Rahmani, H.; Rasoli, V.; Abdossi, V.; Ghanbari Jahromi, M. (South African Journal of Enology and Viticulture, 2023)
Drought stress is the most important environmental factor limiting the growth, development and yield of crop plants and horticulture. In this study, the induction of drought resistance in commercial cultivars (as scion) by the Ch1 rootstock was evaluated based on physiological and biochemical responses. Factorial experiment was performed in a completely randomised design (CRD) with three replications in the greenhouse. Plant materials consisted of five commercial grapevine cultivars (own-rooted plants of Black seedless, Flame seedless, Turkman seedless, Sultana and Shahani, and the scion of these cultivars grafted onto Ch1 rootstock). Drought stress treatment comprised stopping irrigation for 30 days from July to August, and not stopping irrigation was the control. Drought stress significantly reduced the membrane stability index (MSI) and the relative water content (RWC), and increased electrolyte leakage (EL), catalase, hydrogen peroxide, proline, ascorbic acid, guaiacol peroxidase, protein, sodium and potassium levels (P < 0.05). The EL and MSI in the Ch1 rootstock under drought stress decreased by 18.38% and 14.86% respectively. The Ch1 rootstock significantly increased the amount of proline, total protein and enzyme activity of guaiacol peroxidase and catalase in cultivars in a drought stress environment. The amount of hydrogen peroxide decreased in all cultivars grafted on Ch1 in both drought stress and non-drought stress environments, by 14.3% and 18.9% respectively. Sultana cultivar grafted on Ch1 rootstock showed the highest drought resistance. Therefore, it can be concluded that the Ch1 rootstock is recommended as a rootstock for inducing drought resistance in grapevine cultivar scions.